2017
DOI: 10.1039/c6lc01555g
|View full text |Cite
|
Sign up to set email alerts
|

Formation of surface nanodroplets facing a structured microchannel wall

Abstract: Surface nanodroplets are important units for lab-on-a-chip devices, compartmentalised catalytic reactions, high-resolution near-field imaging, and many others. Solvent exchange is a simple solution-based bottom-up approach for producing surface nanodroplets by displacing a good solvent of the droplet liquid by a poor one in a narrow channel in the laminar regime. The droplet size is controlled by the solution composition and the flow conditions during the solvent exchange. In this paper, we investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Consequently, it is expected that z max B Pe 1/2 and t B h 2 Pe À1/2 /D, reflecting that at a fixed position downstream for large advection velocity the blob of oversaturation will be smeared out less as less time has passed. 20 Thus z max Át B h 2 /D, 20 resulting in…”
Section: Theoretical Analysis Of Droplet Growth Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, it is expected that z max B Pe 1/2 and t B h 2 Pe À1/2 /D, reflecting that at a fixed position downstream for large advection velocity the blob of oversaturation will be smeared out less as less time has passed. 20 Thus z max Át B h 2 /D, 20 resulting in…”
Section: Theoretical Analysis Of Droplet Growth Dynamicsmentioning
confidence: 99%
“…This result demonstrates the mixing behaviour during solvent exchange is well described Taylor-Aris dispersion. [20][21][22][23]…”
Section: Theoretical Analysis Of Droplet Growth Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…As many natural and synthetic surfaces are structured, 14,15 it is of high interest to use the potency of morphology for controlling heterogeneous nucleation. Previous studies showed the power of geometry in nucleation of droplets from vapor [16][17][18] or solutions, 19 and in shaping foams in 2D. 20 Yet, the impact of surface micromorphology and curvature on bubble nucleation under flow was not experimentally studied.…”
Section: Introductionmentioning
confidence: 99%